Pendidikan kesehatan dalam rangka menuju panti asuhan bebas pedikulosis kapitis di Kecamatan Siak Hulu Kabupaten Kampar - Esy Maryanti; Enny Lestari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Pediculosis capitis is a parasitic disease that still often occurs and neglected. Clinical symptoms of this disease are itching on the head that can interfere with daily activities. The orphanage is house to a group of children who live together and is a place at risk for parasitic infestations. This activity aims to determine the incidence of Pediculus humanus capitis infestation, conduct health education in the determine the incidence of the disease, conduct health education in the form of counselling and training to prevent the disease and management of children with pediculosis. This activity was carried out at the orphanage in Pandau Jaya Village, Siak Hulu District, Kampar Regency. The target subject is all 60 children and caretakers, and the specific target is 54 children of the orphanage. There were 22 (40.7%) children infected with Pediculus humanus capitis. Infected children are given therapy by permethrine 1%. Also given a comb, one child one comb. After the education and training of children and caretakers are expected to be able to apply the knowledge gained so that it can eradicate the disease.